Produções videogravadas em Libras e infância surda: uma análise tradutória da cantiga “A canoa virou” - Tedesco, Sabrina Marchezani (Universidade Federal de São Carlos, 2026)
The presence of the Brazilian Sign Language (Libras) interpreter in the artistic and cultural sphere, particularly in the field of musical translation for deaf children, remains an emerging area within professional training, despite the growing demand for cultural accessibility from the earliest years of life. Early childhood education, a stage strongly characterized by musical experiences, contrasts with the scarcity of productions that integrate musicality, visuality, and playfulness in Libras, a gap that directly impacts the work of educational translators and interpreters in this field. In light of this scenario, this Undergraduate Thesis, developed within the Bachelor's Degree in Translation and Interpreting in Brazilian Sign Language and Portuguese (TILSP), aims to analyze the translation process of the verbal and non-verbal elements of the traditional Brazilian children's folk song A Canoa Virou ("The Canoe Capsized"). The study investigates the visual, bodily, spatial, and expressive strategies employed in the original version, created for hearing audiences, seeking to reinterpret them into a visual, cultural, and linguistic experience directly connected to deaf childhood. The research is grounded in Deaf Studies and in studies on deferred textuality, literacies, multiliteracies, and multimodalities, understanding deafness as a linguistic and cultural difference and signed musical translation as a process of aesthetic, poetic, and performative creation. As a result, the study presents an analysis of the strategies employed throughout the translation process of the folk song, with the aim of producing adapted educational materials for professionals in the field of education, particularly those working in bilingual early childhood education for deaf children in the Brazilian context.
Video-recorded productions in Brazilian Sign Language and deaf childhood: a translation analysis of the children’s song “The canoe capsized”
Keywords: Libras; Infância surda; Tradução musical; Filosofia da diferença; Cantiga popular; CIENCIAS SOCIAIS APLICADAS::COMUNICACAO::COMUNICACAO VISUAL; CIENCIAS SOCIAIS APLICADAS::DIREITO::DIREITOS ESPECIAIS; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO; 4. Educação de Qualidade